STRATEGI GURU BK MEMBERIKAN PEMAHAMAN BAHAYA PENYALAHGUNAAN NARKOBA PADA SISWA - Zefrullah Rana Sagala; Khairuddin Tambusai (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research began with the increasing increase in drug abuse among teenagers, especially students at school. The problems studied in this research are 1) How to understand the dangers of drug abuse, 2) How the counseling teacher's strategy provides an understanding of the dangers of drug abuse and, 3) What factors support and hinder the counseling teacher's strategy in providing an understanding of the dangers of drug abuse to students. The approach used in this research is a qualitative approach with a descriptive type of research. The informants in this research consisted of school principals, teachers and BK. Data collection was carried out using interview, observation and documentation techniques. The results of the research show that the guidance counselor's strategy for providing understanding of the dangers of drug abuse to students is to collaborate with various teachers at school, instill spiritual, moral and social values in students, direct students to positive things and conduct socialization about the dangers of drugs, and guidance counselors provide the right understanding of the dangers of drug abuse for students. Meanwhile, the obstacles for guidance and counseling teachers in providing an understanding of the dangers of drug abuse to students are the lack of student awareness of drug and drug addiction, the lack of support from students' families, especially parents, to control their children, and limited facilities and infrastructure in dealing with drugs.